2010
DOI: 10.5050/ksnve.2010.20.12.1128
|View full text |Cite
|
Sign up to set email alerts
|

An Electro-magnetic Air Spring for Vibration Control in Semiconductor Manufacturing

Abstract: One of the typical problems in the precise vibration is resonance characteristics at low frequency disturbance due to a heavy mass. An electro-magnetic(EM) air spring is a kind of vibration control unit and active isolator. The EM air spring in this study aims at removing the low frequency resonance for semiconductor manufacturing. The mechanical and electronic parts in the active isolator are designed to operate under a weight of 2.5 tons. The EM spring is floated using air pressure in a pneumatic elastic cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The hybrid mount is a kind of mechanical device that has a parallel connection of an isolator and MR damper. The machine body levitated via the pneumatic pressure and was supported by the hybrid mounts which isolate the floor from vibration by means of a long settling time [25]. The MR damper was fixed in the center of the air chamber that was formed with a high-elasticity rubber.…”
Section: Structure Of the Hybrid Mountmentioning
confidence: 99%
“…The hybrid mount is a kind of mechanical device that has a parallel connection of an isolator and MR damper. The machine body levitated via the pneumatic pressure and was supported by the hybrid mounts which isolate the floor from vibration by means of a long settling time [25]. The MR damper was fixed in the center of the air chamber that was formed with a high-elasticity rubber.…”
Section: Structure Of the Hybrid Mountmentioning
confidence: 99%
“…Kim et al 6 studied EMASVI for several years and in their design electromagnetic actuator was mounted in air chamber of air spring. It was concluded that after implementing active control, impulse response delay time decreased 77%, resonance frequency of the system improved, and the vibration peak reduced 62%.…”
Section: Introductionmentioning
confidence: 99%
“…The air mount must satisfy the vibration criteria of the floor vibration, and should also absorb the machine vibration quickly. We have been developing air mounts based on pneumatic and EM forces for precision machines in clean rooms [12,13]. The air mount is a kind of active air spring in which EM actuators are present within a pneumatic system.…”
Section: Introductionmentioning
confidence: 99%